Killing Contention : Demobilization in Morocco during the Arab Spring - Badran, Sammy Zeyad (Book collections on Project MUSE., 2022)
"Badran examines how state polices can divide and effectively kill a social movement. Interviews with the February 20 Movement, the main organizer of mass protests in Morocco from 2011-12, reveal how reforms along with limited repression ultimately divided and weakened the movement"--